Tinjauan Hukum Ekonomi Syariah terhadap Akad Pembulatan Timbangan Pada Jasa Pengiriman Barang - Rachmawati, Andini; Awalia, Fadhila Tianti Mudi; Aqidah, Nurul (el hisbah Journal of Islamic Economic Law, 2024)
The development of e-commerce in Indonesia has also driven the growth of the shipping industry, including J&T Express, which is present with an innovative distribution system and shipping tariff determination based on rounding of the weight of the goods. The method of determining the tariff through rounding of weight creates the potential for a discrepancy between the actual weight of the goods and the tariff charged to consumers, thus potentially creating injustice in transactions. This study aims to analyze the implementation of the contract in the practice of rounding off the scales at J&T Express and to examine its compliance with the principles of Islamic economic law. This study uses a qualitative and conceptual approach. Data collection techniques are carried out through observation, in-depth interviews with the management and customers of the J&T Express Madiun branch, and documentation of the shipping tariff determination policy. The data obtained are analyzed descriptively-analystically using the theory of the ijarah contract in Islamic economic law. The results of the study indicate that the practice of rounding off the weights in the J&T Express Madiun branch delivery service is generally in accordance with the principles of Islamic economic law, because the pillars and valid requirements of the ijarah contract have been fulfilled, the determination of the ujrah is based on an agreement between the service provider (mu'jir) and the service user (musta'jir), the existence of the principle of justice in the implementation of transactions, and the achievement of benefits for the parties to the contract. In addition, consumers did not object to the rounding system, and the ujrah agreement was considered not to contain elements of exploitation.